P=[tex]\frac{1}{2} *a*h[/tex]
a)
[tex]4^{2} + x^{2} =12^{2} \\16 + x^{2} = 121\\x^{2} = 121-16\\x^{2} = 105\\x =\sqrt{105}[/tex]
P = 1/2*12*[tex]\sqrt{105}[/tex] = 6[tex]\sqrt{105}[/tex]
b)
[tex]5^{2} + x^{2} =14^{2} \\25+ x^{2} = 196\\x^{2} = 196-25\\x^{2} = 171\\x =\sqrt{171}[/tex]
P = 1/2*14*[tex]\sqrt{171}[/tex] = 7[tex]\sqrt{171}[/tex]
c)
[tex]6^{2} + x^{2} =9^{2} \\36+ x^{2} = 81\\x^{2} = 81-36\\x^{2} =45 \\x =\sqrt{45} \\x = 3\sqrt{5}[/tex]
P = 1/2*9*3*[tex]\sqrt{5}[/tex] = 13,5[tex]\sqrt{5}[/tex]
d)
[tex]7^{2} + x^{2} =5^{2} \\49+ x^{2} = 25\\x^{2} = 25-49\\x^{2} =- 24\\x =-\sqrt{24} \\x = -2\sqrt{6}[/tex]
P = P = 1/2*5*(-2[tex]\sqrt{6}[/tex]) = -5[tex]\sqrt{6}[/tex]
Mam nadzieję, że pomogłam i że jest już dobrze w razie problemów inf w komentarzu.